Causes and Management of Insect and Mite Resistance in Strawberry Production - James F. Price; Elzie McCord, Jr.; Curtis Nagle (EDIS)
ENY-841, a 6-page fact sheet by James F. Price, Elzie McCord, Jr., and Curtis Nagle, defines pesticide resistance, how it is established and resistance management. Includes tables summarizing modes of action for pesticides used in Florida strawberry production. Published by the UF Department of Entomology and Nematology, November 2007.